Applying User-Centered Design Methods to Understand Users' Day-to-Day Experiences Can Inform a Mobile Intervention for Binge Eating and Weight Management - Graham, Andrea K.; Neubert, Sarah W.; Chang, Angela; Liu, Jianyi; Fu, Emily; Green, Emilie A.; Kornfield, Rachel; Nicholas, Jennifer (Frontiers in Digital Health, 2021)
Introduction: Weight loss apps to date have not directly addressed binge eating. To inform the design of a new mobile behavioral intervention that addresses binge eating and weight management, we applied user-centered design methods to qualitatively assess how target intervention consumers experience these conditions in their day-to-day lives. Methods: Participants were 22 adults with self-reported obesity (BMI ≥30) and recurrent binge eating (≥12 episodes in 3 months) who were interested in losing weight and reducing binge eating. Participants completed a digital diary study, which is a user-centered design technique for capturing individuals’ day-to-day experiences in relevant contexts. Qualitative data describing participants’ experiences with binge eating and obesity were analyzed using thematic analysis. Results were then used to create personas (i.e., character archetypes of different intervention consumers). Results: Participants described triggers for binge eating and indicated that binge eating and excess weight negatively impact their mental health, physical health, and quality of life. The resulting personas reflected five different struggles individuals with these health problems experience in managing their binge eating and weight. Conclusions: Individuals with binge eating and obesity have varying precipitants of problematic eating, as well as varying motivations for and challenges to behavior change. To meet the needs of all who seek intervention, an ideal intervention design will account for variations in these factors and be relevant to diverse experiences. Insights from the diary study and resulting personas will inform the next phases of the user-centered design process of iteratively designing prototypes and testing the intervention in practice.